Clinical Review of Pharmacopuncture Therapy Based on the Progression of Bell's Palsy - You Jung Lee; Yeon Ah Choi; Soo Min Ryu; Seung Min Lee; Eun Yong Lee; Cham Kyul Lee; Na Young Jo; Jeong Du Roh (MEDrang Inc., 2021)
There were 26 Bell's palsy cases at the Jecheon Hospital of Korean medicine, Semyung University from February 1, 2019, to February 28, 2021 reviewed. One group (A group) was treated with Bamboo salt pharmacopuncture and cervi cornu parvum pharmacopuncture (CC) pharmacopuncture in the paralyzed side of the face, and the other (B group) group was treated with Soyum pharmacopuncture, and hominis placenta (HP) pharmacopuncture. Amid a paucity of studies that have used bamboo salt and CC pharmacopuncture to treat Bell's palsy, this study aimed to demonstrate possibility of treatment effect on Bell's palsy. In addition, this study was to see if the effect of determine a change in pharmacopuncture was changed according to the progress of Bell's palsy symptoms was effective. Bell's palsy was improved in each group. Altough there were no significant differences in improvement between two groups, Bamboo salt pharmacopuncture and CC pharmacopuncture could be expected to be effective on the paralyzed face. Furthermore, it is effective to switch pharmacopuncture according to the progress of Bell's palsy.